Phenotype standardization for statin-induced myotoxicity. - Alfirevic, A; Neely, D; Armitage, J; Chinoy, H; Cooper, R; Laaksonen, R; Carr, D; Bloch, K; Fahy, J; Hanson, A; Yue, Q; Wadelius, M; et al. (2014)
Statins are widely used lipid-lowering drugs that are effective in reducing cardiovascular disease risk. Although they are generally well tolerated, they can cause muscle toxicity, which can lead to severe rhabdomyolysis. Research in this area has been hampered to some extent by the lack of standardized nomenclature and phenotypic definitions. We have used numerical and descriptive classifications and developed an algorithm to define statin-related myotoxicity phenotypes, including myalgia, myopathy, rhabdomyolysis, and necrotizing autoimmune myopathy.